Little book of screenprinting - Williamson, Caspar (San Francisco : Chronicle Books, 2011)
"Featuring impressive portfolios from today's most cutting-edge studios, along with a compact history of the craft and a guide to different presses and techniques, this comprehensive little volume is a celebration of a printing renaissance."--P. [4] of cover.
Foreword --A short history --Screenprinting in practice --Portfolios --Resources --Contact details.
Includes index.
Keywords: Screen process printing; Serigraphy